Geospatial modelling of the future urban expansion map using AHP and GIS in Bordj Bou Arreridj, Algeria - Hanane Boutaghane; Khalfallah Boudjemaa; Salim Dehimi (Brawijaya University, 2022)
The study aimed to determine the areas of future urban expansion in Bordj Bou Arreridj, Algeria, by using multi-criteria analysis for decision-making. First, the future population was estimated to calculate the area we would need for the horizon of 2041AD. Second, criteria that contribute to determining the best areas for future expansion were selected based on recent research literature. Six factors were adopted: (industrial areas, agricultural lands, urban areas, road network, slopes, and hydrographic network). Third, the analytic hierarchy process (AHP) was used to make a comparison of the previous standards and to extract the weights. Fourth, translating the results obtained in the (QGIS) program and extracting a digital map showing areas suitable for future urban expansion according to three classifications (high spatial suitability, acceptable, and low). The results showed that the areas with high spatial suitability it densely distributed in the northeastern and western directions with an area of 12.42 km² or 23%. It is considered an insufficient area to meet the future need of 2041 AD, which amounted to 14.20 km². Followed by areas with acceptable suitability distributed in four geographical directions, occupying an area of 15.67 km² or 35%, which is a sufficient area and can be placed as a balance to fill the deficit. While the areas with low suitability densely distributed in the east-west sides, with an area of 16.26 km² or 37%. The research proved that the integration between (AHP) and (GIS) technologies have an important role in helping decision-makers identify suitable areas for future expansion, reduce the problems of random urbanization and create a homogeneous sustainable environment. Urban development in the future.